A cadmium-based metal complex for hydrogen production by alkaline electrolysis of water, and a preparation method and application thereof

CN122978145APending Publication Date: 2026-10-27JINGGANGSHAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611165564.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

第一,电催化活性优异——线性伏安测试显示该配合物在碱性介质中具有较低的析氢过电位和较小的Tafel斜率,产氢效率高,得益于一维异金属链提供的快速电子传输通道和双金属协同效应对氢吸附自由能的优化。第二,稳定性突出——恒电流充放电测试表明,在10mA/cm2电流密度下持续反应10小时后,催化活性未发生明显衰减,说明配合物在强碱性电解液和长期电解条件下结构稳定,具有实际应用潜力。第三,结构优势独特——配合物堆积形成的多孔三维网络增大了比表面积,暴露更多活性位点,同时层状晶体形态(SEM证实)有利于电解液渗透和气体释放。第四,制备方法简单温和——水热法反应,无需高温高压或复杂设备,原料易得,乙醇-水体系绿色环保,结晶过程可控,易于放大生产。第五,成本低廉——以丰富的镉、钙和有机配体替代贵金属铂,大幅降低催化剂成本,为碱性电解水制氢工业化推广提供了经济可行的材料方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978145A_ABST
    Figure CN122978145A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrocatalysis of water electrolysis hydrogen production, and more particularly relates to a cadmium-based metal complex for alkaline water electrolysis hydrogen production as well as a preparation method and application thereof. n The cadmium-based metal complex [CaCd2(L)4(AcO)2(H2O)2] provided by the application belongs to a monoclinic crystal system C2 / m space group, is alternately bridged by Cd(II) and Ca(II) through a mu2-carboxylate to form a one-dimensional heterometallic chain, and produces a porous three-dimensional network after stacking. The cadmium-based metal complex can be obtained by ultrasonic mixing of 2-methyl-3-hydroxyquinoline-4-carboxylic acid, ethanol and water, adding cadmium acetate and calcium carbonate, and reacting at 70-90 DEG C for 2-4 days, and then taking supernatant to stand and crystallize, and can be used as an electrocatalyst for alkaline water electrolysis hydrogen evolution reaction. The cadmium-based metal complex is mixed with acetylene black and polytetrafluoroethylene emulsion to be loaded on a foamed nickel to form an electrode, and the electrode exhibits excellent hydrogen production activity and stability in a KOH solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic technology for hydrogen production by water electrolysis, and more specifically, relates to a cadmium-based metal complex for alkaline water electrolysis hydrogen production, its preparation method, and its application. Background Technology

[0002] In today's era, the global population continues to grow, human activities are becoming increasingly frequent, technology is constantly advancing, and living standards are continuously improving. This has led to a significant increase in total energy consumption. Currently, global primary energy demand relies mainly on fossil fuels, whose resources are being rapidly depleted, resulting in current price fluctuations and market instability. The widespread use of non-renewable energy sources such as coal, oil, and natural gas continues to emit greenhouse gases such as carbon dioxide, methane, sulfur dioxide, and nitrous oxide. These emissions cause various environmental problems, including acid rain, air pollution, increased tropospheric ozone concentration, stratospheric ozone layer depletion, the greenhouse effect, and global warming. To address these challenges, the world is actively promoting the replacement of non-renewable resources with sustainable and environmentally friendly energy sources. Although renewable energy sources such as solar, wind, tidal, and biomass energy exist, they face the challenge of intermittent availability due to regional or seasonal factors. Therefore, there is an urgent need to develop efficient energy conversion and storage systems to support the large-scale application of renewable energy. Among many alternatives, hydrogen energy stands out as a highly promising new energy source and represents a direction for the development of human energy strategy.

[0003] The choice of hydrogen production method is crucial for the widespread use of hydrogen energy. Currently, water electrolysis is a widely used method for producing hydrogen in industrial production due to its simple process equipment, and it is also an important research direction. The hydrogen evolution reaction (HER), using Pt / C catalysts as the benchmark catalyst in the core step of water electrolysis, has extremely limited practical application due to its high cost and scarcity. Therefore, developing a cost-effective, efficient, and durable non-precious metal HER electrocatalyst is crucial for promoting the development of water electrolysis technology. Summary of the Invention

[0004] The purpose of this invention is to provide a cadmium-based metal complex for alkaline water electrolysis to produce hydrogen, its preparation method, and its application.

[0005] This invention provides a cadmium-based metal complex with the chemical formula [CaCd2(L)4(AcO)2(H2O)2]. n Where L is 2-methyl-3-hydroxyquinoline-4-carboxylic acid, Ac is CH3COH, and n≥1.

[0006] The cadmium-based metal complex [CaCd2(L)4(AcO)2(H2O)2]n synthesized in this invention contains a crystallographically independent Cd(II) center and a crystallographically independent Ca(II) center. The Cd(II) center is in a six-coordinate distorted octahedral environment, consisting of four carboxylic acid oxygen atoms and two μ2-carboxylic acid oxygen bridges. The Ca(II) center is also six-coordinate octahedral, with all coordination sites occupied by μ2-carboxylic acid oxygen atoms. Adjacent Cd(II) centers and Ca(II) centers are alternately bridged by μ2-carboxylic acid groups, forming a one-dimensional (1D) heterometallic chain along a specific direction. This structure effectively improves the electron transport velocity during hydrogen production, and the synergistic effect of the bimetallic structure optimizes the hydrogen adsorption free energy, further increasing the reaction rate. When the one-dimensional heterometallic chains of the cadmium-based metal complex are stacked, they form a porous three-dimensional network, significantly increasing the specific surface area and the exposure of active sites.

[0007] Furthermore, the crystals of the cadmium-based metal complex belong to the monoclinic crystal system. C Space group 2 / m, cell parameters are: a =14.6256(5)Å, b =18.3465(5)Å, c =9.6618(3)Å, α =90°, β =115.367(3)°, γ =90°, Z=2.

[0008] This invention also provides a method for preparing cadmium-based metal complexes, comprising the following steps: mixing 2-methyl-3-hydroxyquinoline-4-carboxylic acid, ethanol and water, and then sonicating to obtain a mixed solution; adding cadmium acetate and calcium carbonate to the mixed solution and sonicating to obtain a mixture; reacting the mixture at 70-90°C for 2-4 days, then allowing it to cool naturally and stand to separate into layers; taking the supernatant and letting it stand at 20-30°C for 3-5 days to precipitate yellow crystals, which are the cadmium-based metal complexes; The mass-to-volume ratio of the 2-methyl-3-hydroxyquinoline-4-carboxylic acid, ethanol, water, cadmium acetate, and calcium carbonate is 0.1~0.3g:4~6mL:9~11mL:0.1~0.3g:0.1004g.

[0009] Furthermore, the ultrasonic treatment has a power of 50-70W and a duration of 4-6 minutes.

[0010] The present invention also provides an electrocatalyst, which is prepared by mixing a cadmium-based metal complex, acetylene black and a polytetrafluoroethylene emulsion with a mass fraction of 9% to 11% at a mass ratio of 6 to 8: 1 to 3: 1.

[0011] The present invention also provides an electrode prepared by loading the electrocatalyst onto nickel foam.

[0012] The present invention also provides the application of the electrode in the hydrogen evolution reaction, wherein the electrode serves as a working electrode in an alkaline electrolyte to carry out the hydrogen evolution reaction.

[0013] Furthermore, the alkaline electrolyte is an aqueous solution of potassium hydroxide or sodium hydroxide with a concentration of 0.5–1.5 mol / L.

[0014] The present invention has the following beneficial effects: First, it exhibits excellent electrocatalytic activity—linear voltammetry shows that this complex has a low hydrogen evolution overpotential and a small Tafel slope in alkaline media, resulting in high hydrogen production efficiency. This is attributed to the fast electron transport channel provided by the one-dimensional heterometallic chain and the optimization of the hydrogen adsorption free energy by the bimetallic synergistic effect. Second, it demonstrates outstanding stability—constant current charge-discharge tests show that at 10 mA / cm²... 2 After 10 hours of continuous reaction at the current density, the catalytic activity did not show significant attenuation, indicating that the complex is structurally stable under strongly alkaline electrolyte and long-term electrolysis conditions, and has practical application potential. Third, it has unique structural advantages—the porous three-dimensional network formed by the complex stacking increases the specific surface area, exposing more active sites, while the layered crystal morphology (confirmed by SEM) facilitates electrolyte permeation and gas release. Fourth, the preparation method is simple and mild—the hydrothermal reaction does not require high temperature, high pressure, or complex equipment; the raw materials are readily available; the ethanol-water system is environmentally friendly; the crystallization process is controllable; and it is easy to scale up production. Fifth, it is low-cost—by replacing the precious metal platinum with abundant cadmium, calcium, and organic ligands, the catalyst cost is significantly reduced, providing an economically feasible material solution for the industrial-scale promotion of alkaline water electrolysis for hydrogen production. Attached Figure Description

[0015] Figure 1 This is a crystal structure diagram of a cadmium-based metal complex.

[0016] Figure 2 This represents an infinite chain diagram formed by cadmium-based metal complexes in their crystal stacking.

[0017] Figure 3 This is a scanning electron microscope image of a cadmium-based metal complex.

[0018] Figure 4 Linear voltammetric hydrogen production curves for cadmium-based metal complexes.

[0019] Figure 5 A graph showing the stability of hydrogen production cycles for cadmium-based metal complexes. Detailed Implementation

[0020] The present invention will now be described in detail with reference to specific embodiments, but these should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following embodiments can be obtained commercially unless otherwise specified.

[0021] Example 1: Preparation and characterization of cadmium-based metal complexes.

[0022] I. Preparation of cadmium-based metal complexes.

[0023] 0.2027 g of 2-methyl-3-hydroxyquinoline-4-carboxylic acid, 5 mL of ethanol, and 10 mL of H₂O were mixed in a 25 mL polytetrafluoroethylene-lined high-pressure reactor and sonicated at 60 W for 5 min. After sonication, 0.2223 g of cadmium acetate and 0.1004 g of calcium carbonate were added to the mixture, and sonication was continued at 60 W for 5 min. The mixture was reacted at 80 °C for 3 days. After natural cooling and standing to separate the layers, the supernatant was collected and allowed to stand at 25 °C for 4 days, after which yellow crystals precipitated, which were the cadmium-based metal complex.

[0024] II. Characterization of cadmium-based metal complexes.

[0025] 1. X-ray single crystal diffraction Experimental Methods: Single crystals with intact morphology, free from cracks and impurities, were selected and fixed at the center of the diffractometer's goniometer using a crystal carrier. X-ray single-crystal diffraction data were obtained using a SuperNova CCD X-ray diffractometer with a microfocus sealed X-ray tube as the radiation source, Mo-Kα radiation as the radiation type (λ=0.71073nm), and a diffraction monochromator as the mirror. Data processing and empirical absorption correction were performed using CrysAlisPro software 1.171.39.46 (Rigaku OD, 2018). The crystal structure was resolved using the direct method of SHELXL-2018 / 3, and the final structure was refined at F2 using the full-matrix least squares method.

[0026] Experimental results: From the crystal structure diagram ( Figure 1 It can be seen that the cadmium-based metal complex [CaCd2(L)4(AcO)2(H2O)2] was prepared by hydrothermal method. n (L = 2-methyl-3-hydroxyquinoline-4-carboxylic acid, Ac = CH3COH) a =14.6256(5)Å, b =18.3465(5)Å, c =9.6618(3)Å, α =90°, β =115.367(3)°, γ=90°, Z=2, R1=0.0267, wR2=0.0646, GooF=1.059, crystal data are listed in Table 1, while key bond lengths and bond angles are shown in Tables 2 and 3. It contains a crystallographically independent Cd(II) center (occupancy 0.5) and a crystallographically independent Ca(II) center (occupancy 0.25). Cd(I) is in a six-coordinate distorted octahedral environment, consisting of four carboxylic acid oxygen atoms and two μ The 2-carboxylic acid oxygen bridge is formed, and Ca(1) has a six-coordinate octahedral configuration, with all coordination sites being... μ The 2-carboxylic acid oxygen atom occupies the bond. All Cd–O and Ca–O bond lengths are consistent with those of the previously reported cadmium carboxylate and calcium carboxylate systems. Adjacent Cd(1) and Ca(1) centers are connected by... μ Alternating 2-carboxylate bridging links form one-dimensional (1D) heterometallic chains along specific directions. Figure 2 ).

[0027] Table 1: Crystal Data Table 2: Critical Bond Lengths Table 3: Key Bond Angles Note: / indicates no data.

[0028] 2. Scanning electron microscope (TEM) Experimental Method: The sample to be tested was selected and fixed to the sample stage with conductive adhesive. The sample surface was then coated with gold for conductivity. The sample stage was moved into the vacuum chamber of the scanning electron microscope and evacuated to a high vacuum state. Parameters such as accelerating voltage and working distance were set, and the sample surface was scanned point by point using a focused electron beam to excite secondary electrons and backscattered electron signals. The signals were collected and amplified by a detector and converted into imaging signals to observe the microstructure, size, and surface structure of the sample. Clear microscopic images were captured and saved for analysis.

[0029] Experimental results: Scanning electron microscope images ( Figure 3 The crystal exhibits a layered morphology with an uneven surface, obvious traces of layered peeling, local protrusions and defect areas, a small number of in-phase microcrystalline particles attached, and cracks. It is a typical layered crystal structure.

[0030] Example 2: Application of cadmium-based metal complexes.

[0031] I. Preparation of working electrode.

[0032] A 1cm×1cm piece of nickel foam was immersed in a 1 M hydrochloric acid solution and sonicated for 5 minutes to remove oil and surface oxide layer. Then it was ultrasonically cleaned with deionized water for 5 minutes to obtain a clean nickel foam substrate. The nickel foam substrate was then placed in a vacuum drying oven and dried at 70°C for 30 minutes to obtain the processed nickel foam substrate.

[0033] The obtained cadmium-based metal complex, acetylene black, and 10% polytetrafluoroethylene emulsion were mixed evenly at a mass ratio of 7:2:1 and then evenly coated onto the surface of the treated nickel foam substrate. The coated nickel foam was placed in a vacuum drying oven and dried at 110°C for 10 hours. After cooling to 25°C, it was taken out and pressed into a thin sheet with a gravity of 5N using a hydraulic press, which served as the sample electrode.

[0034] II. Electrochemical hydrogen production performance test.

[0035] Testing instrument: Electrochemical workstation Test method: A three-electrode system was used, with the sample electrode as the working electrode, the Ag / AgCl electrode as the reference electrode, and the graphite rod as the counter electrode. The electrolyte was a 1 mol / L KOH solution. The linear voltammetric curve of the material was measured after purging with nitrogen for 30 min.

[0036] Linear Voltammetry (LSV) Testing: This test is conducted using an electrochemical workstation with a scan rate of 5 mV / s and a potential window of -1.3 to -0.6 V. A linearly varying potential is applied to the working electrode, and the change in current with respect to this potential is recorded. In LSV testing, the electrochemical workstation linearly scans the potential of the working electrode at a constant rate, simultaneously recording the change in the current flowing through the electrode. The result is a curve reflecting the relationship between current and potential, also called an LSV curve / voltammetric plot. The overpotential in the LSV curve and the slope of the resulting Tafel curve (Tafel slope) are used to assess the OER catalytic performance of the tested material.

[0037] Stability testing: Constant current charge-discharge (GCD) experiments were conducted using an electrochemical workstation to evaluate the battery's charge-discharge performance at a current density of 10 mA / cm². 2 The test lasted for 10 hours. Stability testing determines whether the material can maintain good performance under prolonged operation or environmental changes, avoiding performance degradation, failure, or other instability. The test potential was converted to a standard hydrogen electrode, using the formula: E(RHE) = E(Ag / AgCl) + 0.197V + 0.059pH.

[0038] Experimental results: Figure 4 The linear voltammetry curves of the samples show that the cadmium-based metal complex catalyst exhibits excellent activity for hydrogen production through water electrolysis. Figure 5The sample stability curves show that at a current density of 10 mA / cm², 2 Under the specified conditions, the activity of the cadmium-based metal complex catalyst did not change significantly after 10 hours of reaction. This indicates that the prepared cadmium-based metal complex catalyst has good stability.

[0039] It should be noted that when numerical ranges are mentioned in the claims of this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. To avoid redundancy, the present invention describes preferred embodiments.

[0040] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0041] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A cadmium-based metal complex, characterized in that, The chemical formula is [CaCd2(L)4(AcO)2(H2O)2]. n Where L is 2-methyl-3-hydroxyquinoline-4-carboxylic acid, Ac is CH3COH, and n≥1.

2. The cadmium-based metal complex according to claim 1, characterized in that, The crystals of the cadmium-based metal complex belong to the monoclinic crystal system. C Space group 2 / m, cell parameters are: a =14.6256(5)Å, b =18.3465(5)Å, c =9.6618(3)Å, α =90°, β =115.367(3)°, γ =90°, Z=2.

3. The method for preparing the cadmium-based metal complex according to claim 1, characterized in that, Includes the following steps: A mixed solution was obtained by ultrasonic treatment after mixing 2-methyl-3-hydroxyquinoline-4-carboxylic acid, ethanol and water. Cadmium acetate and calcium carbonate were added to the mixed solution and ultrasonic treatment was performed to obtain a mixture. The mixture was reacted at 70~90℃ for 2~4 days and then allowed to cool naturally and stand to separate into layers. The supernatant was taken and allowed to stand at 20~30℃ for 3~5 days to precipitate yellow crystals, which are cadmium-based metal complexes. The mass-to-volume ratio of the 2-methyl-3-hydroxyquinoline-4-carboxylic acid, ethanol, water, cadmium acetate, and calcium carbonate is 0.1~0.3g:4~6mL:9~11mL:0.1~0.3g:0.1004g.

4. The preparation method according to claim 3, characterized in that, The ultrasonic treatment has a power of 50-70W and a duration of 4-6 minutes.

5. An electrocatalyst, characterized in that, The electrocatalyst is prepared by mixing a cadmium-based metal complex, acetylene black, and a polytetrafluoroethylene emulsion with a mass fraction of 9% to 11% at a mass ratio of 6 to 8: 1 to 3:

1.

6. An electrode, characterized in that, The electrode is prepared by loading the electrocatalyst onto nickel foam.

7. The application of the electrode according to claim 6 in the hydrogen evolution reaction, characterized in that, The electrode serves as the working electrode in the hydrogen evolution reaction within the alkaline electrolyte.

8. The application according to claim 7, characterized in that, The alkaline electrolyte is a potassium hydroxide aqueous solution or a sodium hydroxide aqueous solution with a concentration of 0.5–1.5 mol / L.